Extraction and Characterization of Natural Fibers from Citrullus lanatus Climber. Issue 2 (1st February 2022) - Khan, Anish; Vijay, R; Singaravelu, D Lenin; Sanjay, M R; Siengchin, Suchart; Jawaid, Mohammad; Alamry, Khalid A.; Asiri, Abdullah M.
ABSTRACT: The growing environmental awareness toward the replacement of non-biodegradable materials with biodegradable materials has led many researchers for looking at many bio-based materials to suit various applications. This study objective to evaluate the morphology and properties of fibers extracted from Citrullus lanatus climber. The physical-chemical, thermal, mechanical, crystalline, morphological characteristics of Citrullus lanatus climber fibers were examined by Fourier transform-infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), single fiber tension test, X-ray diffraction (XRD), and scanning electron microscope (SEM). The test results showed cellulose content (53.7 wt. %), density (1227 kg/m 3 ), crystallinity index (33.33%) which prove that Citrullus lanatus climber fibers can be used as reinforcement for light-weight medium load applications.